Donut Product Marketing Strategy in Increasing Sales at Domami Stores, Manggala District, Makassar City - Mochtar Luthfi; Norhaedah K; Riska Riska (Universitas Negeri Makassar, 2022)
Research objectives 1 ) To analyze marketing strategies in increasing sales at Domami Stores, Manggala District, Makassar City 2) To determine the supporting factors and inhibiting factors in increasing sales at Domami Manggala Shops, Makassar City. The type of research carried out is with a qualitative descriptive approach. This research was carried out at the Domami Manggala shop located Antang Jl. Nipa-Nipa No. 85b, Manggala District, Makassar City. Data sources are primary and secondary data. The focus of the research is marketing strategy. Data collection techniques are observation, interviews, and documentation. The results of the study explain that 1) The marketing strategy used by Domami Manggala Stores in increasing sales is to apply the concept of marketing mix, starting from product selection, where the products offered are different. different with prices starting from Rp. 15,000 to a price of Rp. 50,000 which can be reached by all people, taking places in strategic locations, and promotions are carried out in 2 ways, namely Online and Offline, Online using social media such as WhatsApp, Instagram, Facebook, Gojek, as for Offline installing shop front banner. 2) Supporting factors are strategic location, product introduction on social media, and the inhibiting factor is decreasing consumer purchasing power and preferring to produce their own